Cattle Market Development as a Strategy for Internally Generated Revenue (IGR) Growth in Adamawa State - Basila, Denis; Gabriel, Raymond (FUDMA JOURNAL OF SCIENCES, 2025)
This study examines strategies for enhancing revenue generation in the cattle market of Adamawa State, Nigeria. Using a mixed-method approach, data were collected from 150 respondents through structured questionnaires and interviews conducted across four major cattle markets: Yola, Mubi, Ganye, and Numan. Quantitative data were analyzed using descriptive statistics, Pearson correlation, and multiple regression, while qualitative responses were assessed through thematic analysis. The results indicate that key factors influencing revenue include market infrastructure, access to veterinary services, and availability of real-time market information, financial support, and transport security. Regression analysis revealed that improved infrastructure (β = 0.48, p < 0.01) and access to credit (β = 0.65, p < 0.01) significantly boost revenue. Correlation results also showed a strong relationship between infrastructure quality and earnings (r = 0.71). Interview insights highlighted recurring challenges such as poor facilities, cattle diseases, lack of pricing transparency, and insecurity during transportation. The study concludes that addressing these constraints through strategic investment in market infrastructure, veterinary services, digital information systems, and access to finance can significantly enhance revenue in the cattle trade. Recommendations are made for collaborative efforts between government agencies, private stakeholders, and local market authorities to improve the efficiency and profitability of the cattle market in Adamawa State.
Keywords: Cattle Market Development; Market Strategy; Internal Revenue; Adamawa State